Effects of Different Postharvest Treatments on Cuticle Microstructure and Components of 'Nanfeng' Mandarins (Citrus reticulata Blanco cv. Kinokuni) During Cold Storage - Sheng CHEN; Shuai GE; Yaohua LUO; Lüzhu YANG; Shuang HE; Rongrong WANG; Shenghua DING (Shipin gongye ke-ji, 2022)
The cuticle plays an important role in postharvest physiology of fruit, and its microstructure and components could be affected by different postharvest storage conditions. Heat shock (HT) and chitosan (CS) treatment have been proved to be effective in delaying fruit decay. In this study, 'Nanfeng' mandarins (Citrus reticulata Blanco cv. Kinokuni) were treated with HT, CS and HT combined with CS (HT+CS), and changes in cuticle microstructure and components during cold storage for 75 d were carried out by scanning electron microscopy (SEM) and gas chromatography-mass spectrometry (GC-MS), respectively. The results showed that irregular platelets waxes were deposited on the surface of 'Nanfeng' mandarins. The epicuticular wax redistributed and filled the cracks on the epidermis of the fruit induced by HT. Totally, 38 different components were identified in the epicuticular wax while 50 different components in intracuticular wax. Epicuticular wax and intracuticular wax for all groups were mainly composed of alkanes, acids, esters, and terpenoids. And all the cutin monomers were acids, including 7 different components. Hexadecanoic acid was the main component in cuticle of 'Nanfeng' mandarins. In general, there was no obvious regular change in the amounts of epicuticular wax, while intracuticular wax decreased firstly and then increased. And the amounts of cutin monomers decreased all the time during cold storage. All 3 treatments significantly inhibited the decline of epicuticular wax and intracuticular wax after 45 d, and effectively inhibited the reduction of cutin monomers all along, especially for the heat shock. In summary, heat shock can maintain the storage quality of 'Nanfeng' mandarins by changing the microstructure and regulating the components of cuticle, which shed new light on improving its postharvest storage quality.